2021
DOI: 10.1158/2159-8290.cd-20-1677
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Bulk and Single-Cell Profiling of Premanufacture T-cell Populations Reveals Factors Mediating Long-Term Persistence of CAR T-cell Therapy

Abstract: reports receiving commercial research grants from Kite, Servier, and Novartis, is listed as inventor on a patent for toxicity management for antitumor activity of CARs (WO 2014011984 A1; managed according to the University of Pennsylvania patent policy), and reports receiving other remuneration from McNaul Ebel. D.M.B. is now an employee of Tmunity Therapeutics, Inc. No potential conflicts of interest were disclosed by the other authors.Research.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
117
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(118 citation statements)
references
References 53 publications
1
117
0
Order By: Relevance
“…166 Combined with bulk and single-cell ATAC sequencing, Chen et al found that IRF7 could affect CAR-T-cell persistence across T-cell subsets by regulating chronic IFN signaling, and that the TCF7 regulon is maintained in effector T cells among patients with long-term CAR-T-cell persistence. 167 The dynamic epigenetic changes in various cell types during the CRS process are also worthy of further study.…”
Section: Cutting-edge Technologies In Crs-related Studies Single-cell Technologiesmentioning
confidence: 99%
“…166 Combined with bulk and single-cell ATAC sequencing, Chen et al found that IRF7 could affect CAR-T-cell persistence across T-cell subsets by regulating chronic IFN signaling, and that the TCF7 regulon is maintained in effector T cells among patients with long-term CAR-T-cell persistence. 167 The dynamic epigenetic changes in various cell types during the CRS process are also worthy of further study.…”
Section: Cutting-edge Technologies In Crs-related Studies Single-cell Technologiesmentioning
confidence: 99%
“…Logo plots showing the relative abundance of conserved nucleotides for several known transcription factors revealed a highly significant association for transcription factors that are coupled to T cell effector and memory differentiation (Figure 1G). Most notably, some of these-including FOS:JUNB, STAT5, and TCF7-have established roles in regulating CAR T cell anti-tumor responses (Lynn et al, 2019;Zheng et al, 2021;Chen et al, 2021). Taken together, these data document the vast changes in DNA methylation that occur in CAR T cells post-infusion and show that these epigenetic events parallel the modifications that arise during endogenous T cell differentiation.…”
Section: Resultsmentioning
confidence: 60%
“…CD19-CAR T cells derived from the less-differentiated central memory T cell subset have been reported to exhibit greater proliferation, contributing to the enhanced survival in pre-clinical murine tumor models (Sommermeyer et al, 2016). In patients receiving CD19-CAR T cell therapy, the pre-manufactured T cell population with higher proportions of the less-differentiated T cell subsets (naive, Tscm and Tcm) was associated with CAR T cell persistence beyond 6 months (Chen et al, 2021). Furthermore, it has recently been shown that CD19-CAR T cell infusion products enriched for gene expression signatures indicative of T cell exhaustion have poor expansion after infusion into patients (Deng et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Another study by Garfall and colleagues also highlighted that higher frequencies of CD8 + CD45RO - CD27 + cells in the leukapheresis product of patients with MM correlated with more proliferation and better CTT responses ( 40 ). Increased frequencies of T N ( 38 ), T CM ( 41 ) and/or T SCM cells ( 42 ) appear to correlate with improved engraftment and/or tumour control in adoptive cell transfer models, probably because they have functional advantages compared to more differentiated, less proliferative subsets. For example, T N cells have been shown to possess longer telomeres, more robust proliferative capacity and generate more functional cells ( 38 ).…”
Section: Lessons From Ctt Biologymentioning
confidence: 99%